IMPLIKATUR PERCAKAPAN DALAM FILM SORE: ISTRI DARI MASA DEPAN: KAJIAN PRAGMATIK GRICE - Nensilianti; Ridwan; Nurul Mutmainnah (Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study is motivated by the limited research exploring implicit meanings in film dialogues from a pragmatic perspective. This study aims to describe conversational implicatures in the film Sore: Istri dari Masa Depan. The study employs a descriptive qualitative method with a pragmatic approach, using dialogue between characters containing implicit meanings as the data. Data were collected through observation and note-taking techniques by repeatedly watching the film and transcribing relevant dialogues. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal various forms of conversational implicatures, including metaphor, hyperbole, indirect warnings, criticism, emotional support, and commitment reinforcement. These implicatures arise due to deviations from cooperative principles in conversation. This study concludes that film dialogues contain complex implicit meanings and serve as a rich object for pragmatic analysis.